Effects of postoperative complications in oesophageal cancer on survival, hospital outcomes, and long-term quality of life: retrospective cohort study - Crnovrsanin, Nerma; Giring, Stefan; Oppel, Antonia; Rompen, Ingmar F.; Schiefer, Sabine; Jorek, Nicolas; Schmidt, Thomas; Müller, Beat P.; Peters, Leila; Nienhüser, Henrik (BJS open, 2025)
Postoperative complications pose a major challenge in oesophageal surgery, affecting survival, recovery, and healthcare resource utilization. The aim of this study was to quantify the proportional contribution of specific complications to survival and adverse outcomes and to evaluate their effects on long-term quality of life (QoL) in patients with oesophageal and gastro-oesophageal junction cancer.This retrospective cohort study included patients with oesophageal or gastro-oesophageal junction cancer who underwent surgery with curative intent between January 2010 and July 2022. Postoperative complications were categorized following Esophageal Complications Consensus Group guidelines. Population-attributable fractions (PAFs) were calculated to estimate the proportion of adverse outcomes and survival effects theoretically preventable if specific complications were avoided.In 632 patients who underwent surgery, the most frequently observed complications were pulmonary (31%), infectious (29%), and gastrointestinal (24%). Pneumonia had the highest adjusted PAF for overall survival (8.3% after 2 years; 95% confidence interval (c.i.) 1.8 to 14.7), suggesting that preventing pneumonia could substantially reduce mortality. Anastomotic leak had the highest PAF for recurrence-free survival (6.6%; 95% c.i. 1.8 to 11.5) and was the complication most significantly contributing to reoperations (PAF 39.8%; 95% c.i. 22.2 to 52.1) and prolonged hospital stays (PAF 56.9%; 95% c.i. 46.8 to 66.2). Respiratory failure had the largest effect on 90-day mortality (PAF 53.5%; 95% c.i. 30.9 to 73.9). In contrast, no significant effect of complications on long-term QoL was observed.This study underscores the critical importance of targeted strategies to prevent postoperative complications, particularly pneumonia and anastomotic leakage, which contribute significantly to adverse outcomes such as reduced survival and prolonged hospital stays. Effective complication management may enhance oncological outcomes and optimize healthcare resource utilization.
Gesehen am 03.12.2025